Quasi-Alliance at Play: The Curious Case of South Korea’s Aborted Withdrawal from GSOMIA in 2019 - Resi Qurrata Aini; Yandry Kurniawan (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to explain why countries maintain security cooperation with a partner even though they are in the middle of severe tensions. This is experienced by the Republic of Korea (ROK), which preferred to maintain its security cooperation with Japan under the General Security of Military Information Agreement (GSOMIA). This research utilizes the concept of abandonment fears to explain South Korea's behavior in reversing its self-declared withdrawal from GSOMIA in 2019. By conducting a deductive-qualitative research approach, this research shows that South Korea was in a position of abandonment fears—fears of being ignored by Japan—magnified by the uncertainty of US commitment. For now, South Korea considers Japan as the most likely partner choice in the region. Thus, Seoul decided to maintain the partnership with Japan within the GSOMIA framework and compromise its grievances with the latter.